2019
DOI: 10.1029/2018ja026272
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Survey of the Terrestrial Bow Shock Observed by the Cluster Spacecraft

Abstract: The terrestrial bow shock provides us with a unique opportunity to extensively investigate properties of collisionless shocks using in situ measurements under a wide range of upstream conditions. Here we report a statistical study of 529 terrestrial bow shock crossings observed between years 2001 and 2013 by the four Cluster spacecraft. By applying a simple timing method to multipoint measurements, we are able to investigate their characteristic spatiotemporal features. We have found a significant correlation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…The terrestrial bow shock is characterized by an abrupt jump in the magnetic field strength as well as the ion number density and velocity when a satellite crosses the bow shock (Kruparova et al, 2019). We select the time interval of the MMS spacecraft in the solar wind by visually identifying the spacecraft entering or leaving the solar wind from the bow shock using the MMS1 data from December 2016 to May 2019.…”
Section: Observationmentioning
confidence: 99%
“…The terrestrial bow shock is characterized by an abrupt jump in the magnetic field strength as well as the ion number density and velocity when a satellite crosses the bow shock (Kruparova et al, 2019). We select the time interval of the MMS spacecraft in the solar wind by visually identifying the spacecraft entering or leaving the solar wind from the bow shock using the MMS1 data from December 2016 to May 2019.…”
Section: Observationmentioning
confidence: 99%
“…The new method has been first applied to the determination of the shape of the Earth's bow shock. The data set for the bow shock normals of 516 Cluster crossing events from Kruparova et al (2019) has been used in this investigation. For most of the cases, the zenith angle α N of the shock normal is less than the corresponding zenith angle α of the crossing points.…”
Section: Discussionmentioning
confidence: 99%
“…Kruparova et al (2019) have investigated 529 terrestrial bow shock crossings between Years 2001 and 2015 observed by the four Cluster spacecraft (Escoubet et al, 2001) (the quasi‐parallel bow shock crossings, which are more turbulent, are not included). The Cluster data can be retrieved from the Cluster Science Archive (Laakso et al, 2010).…”
Section: Application: Determining the Average Geometrical Shape Of Eamentioning
confidence: 99%
See 2 more Smart Citations